VOCATIONAL SCHOOL STUDENTS' PERCEPTIONS OF GOOGLE CLASSROOM IN FULL ONLINE LEARNING AT THE BEGINNING OF THE COVID-19 PANDEMIC - Dantes, Gede Rasben; Rinawati, Ni Komang Ayu; Suwastini, Ni Komang Arie; Artini, Ni Nyoman (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
The global Covid-19 pandemic affects all aspects of life, including students learning process. Teachers and students were instructed to "study from home" using the online learning mode. Many online learning platforms were used during this time, including Google Classroom. The present study aimed to reveal students' perceptions of the implementation of Google Classroom at the beginning of the pandemic. The study took place in one of the state vocational schools in Denpasar City, involving forty students in Grade IX. The data were collected using questionnaires and interviews. The study revealed that most students positively perceived the implementation of Google Classroom in their online learning, even though the sudden shift to online learning. However, students viewed the implementation of Google Classroom in online learning mode lacked interactions during the learning process, causing them to feel that they had no chance to confirm information or knowledge that they had learned. This finding implies that teachers must build interaction between teachers and students during the online learning process.